Blood Pressure measurement from Photo-Plethysmography to Pulse Transit Time - Myint, C.; Lim, Hann; Wong, K.; Gopalai, A.; Oo, M. (2015)
© 2014 IEEE. Blood Pressure (BP) is one of the vital signs in the clinical assessment of patients in both acute and chronic care settings. However, existing BP measurement devices are less portable or invasive and do not allow continuous ambulatory monitoring. In this study, we propose a non-invasive BP-monitoring system using an efficient mathematical model and algorithm to measure the BP by relating Pulse Wave Velocity (PWV) and Pulse Transit Time (PTT) obtained from the Photo-Plethysmography (PPG). An optical system including two sets of PPG sensor probes are used to detect two light reflected signals via finger and wrist. From these PPGs, Pulse Wave Velocity (PWV) and PTT can be estimated to understand the blood flow in the blood vessel. This portable BP monitoring system measures the BP continuously without the need for a cuff and ECG signals. The device does not require a pneumatic cuff and so it facilitates rapid assessment of patients in an acute setting and allows ambulatory self-monitoring of the BP. It also reduces patients' stress and discomfort due to cuff inflations.